Pro-inflammatory cytokines and gelatinases in climatic droplet keratopathy - Holopainen, Juha M. (2012)
PURPOSE. Climatic droplet keratopathy (CDK) is a degenerative disease of the cornea with possible involvement from matrix metalloproteinases (MMPs). Therefore, the authors investigated histologic distribution, levels, and molecular forms of MMP- 2 and MMP-9, as well as tear fluid levels of MMPs and cytokines in CDK patients. They additionally examined UV-B-irradiation effect on production of gelatinases and cytokines by human corneal epithelial (HCE) cell culture model. METHODS. Tears were collected from 20 unrelated individuals (10 with CDK and 10 controls). CDK affected corneas were haematoxylin-eosin stained and the presence and distribution of MMP-2 and MMP-9 was examined using immunohistochemistry. Gelatinases and cytokine secretion was measured in tears and supernatants from UV-B-exposed HCEs by immunoblotting, gelatin zymography, and protein array, respectively. RESULTS. MMP-2 and MMP-9 values were significantly higher in tears collected from CDK patients than healthy controls and were accompanied by pro-inflammatory cytokine secretion. Immunohistochemistry showed that MMP-2 was expressed at the basement membrane zone in both control and affected corneas, but also marked the edges of the granular CDK deposits; MMP-9 expression was restrained to basal layers of the epithelium and was markedly induced in CDK corneas. In HCE cells, UV-B increased gelatinase secretion, with a striking effect on MMP-9, and was preceded by pro-inflammatory cytokine release. CONCLUSIONS. The authors demonstrate that the corneal epithelium could participate in CDK development as a source of cytokines and gelatinases. Additionally, in HCE cells, UV-B- modulated cytokine and subsequent MMP secretion. Local inhibition of cytokine secretion and gelatinases may prevent CDK progression. © 2012 The Association for Research in Vision and Ophthalmology, Inc.